Protestant Bible scholarship: antisemitism, philosemitism and anti-Judaism - Bakker, Arjen; Bloch, René S.; Fisch, Yael; Fredriksen, Paula; Najman, Hindy (Journal for the study of Judaism, 2022)
This volume offers reflections on anti-Semitism, philo-Semitism and anti-Judaism in biblical scholarship from the 19th century to the present. The authors invite us to prepare the way for scholarship that is mindful of its susceptibility to violence and hatred.